Community-Based Gastronomy Tourism Development - The Case Of Northern Thailand - et.al, Niramol Promnil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Gastronomy Tourism Is A Widespread Tourism Trend In Thailand. This Leads The Increasing Number Of Local Restaurants And Menus. This Phenomenon Is Dominated By The Privately Owned- Business And Located In Towns. It Is Neglected Gastronomy Tourism Operated By Local Community, Where The Tourist Can Gain Authentic And Real Local Experiences. Therefore, This Paper Employed A Development Research And Applies A Participatory Action Research (Par) To Initially Develop A Community- Based Gastronomy Tourism Site (Cbgt) In A Second-Tier City In Northern Thailand. This Paper Reveals That Community-Based Tourism (Cbt) Site In Northern Thailand Has A High Potential To Become A Cbgt Site, In Terms Of Community Collaborations, The Variety Of Local Foods, And The Government Supports. Additionally, This Paper Found That Thai Domestic Tourists Are More Likely To Have Their Expections On Affective Experiences Than Cognitive Experience When Visiting A Cbgt Site. Therefore, The Development Of Cbgt In Northern Thailand Applied Affective Experience Components: Happiness, Relaxation, And Nostalgic Feeling, As A Core Experience Offered. However, The Development Is Considered An Incremental Innovation Due To The Lack Of Service Quality And Operational Skills Of The Locals. This Paper Provides Recommendations For Further Cbgt Development And Study.